Multidimensional Self-Organizing Chord-Based Networking for Internet of Things - Ahmed Ismail Abdel Ghafar; Ágeles Vazquez Castro; Mohamed Essam Khedr (International Telecommunications Society (ITS), 2019)
IoT is a coin term recently used in ICT research and industrial community to express the involvement of devices of different capabilities and functionalities in the daily activities of people and organizations. With the enormous amount of data generated by highly dynamic users, the problem of storing, looking up, validating and manipulating data becomes crucial for the success of future networks. A multidimensional chord peer-peer network as extension to the successful chord technology is proposed to cope with the dynamism of IoT networks. Novel approaches have been developed to tackle the high frequency of nodes joining and leaving/failure the network and to deal with Big data, similarity of data, filtering and Geo data.
Keywords: 330; Internet of Things; peer to peer networks; multidimensional chord networks; distributed resource sharing